English (Brazilian Journal of Radiation Sciences, 2022)
The decommissioning of a nuclear power plant is a costly and highly complex process, requiring not only a planning and rigorous chronogram execution as well as funds large enough to cost it. The Long-Term Operation of the plant is not only interesting since it allows the plant to keep producing energy with low-carbon footprint as well as postpone to future these expenses. Around the world several nuclear power plants are being evaluated for Long-Term Operation due to these reasons. In Brazil the oldest nuclear plant, Angra 1, is also being evaluated for Long-Term Operation, otherwise it should be retired/shutdown in next future. However, besides the technical reasons, also the plant’s decommissioning fund seems to be not enough to cost its decommissioning. In the present work, the decommissioning fund of Angra 1 is evaluated considering two different interest rates and compared with the decommissioning cost. The results demonstrates that the Long-Term Operation is necessary and a good decision since it allow an additional time to the provisions on the decommissioning cost increase, avoiding the lack of funds.
Keywords: English